Analisis Pembiayaan berdasarkan Lama Rawat Pasien BPJS Diabetes Melitus Tipe II Komplikasi Sirkulasi Perifer di RSU PKU Muhammadiyah Bantul - Firman, Firman; Lestari, Kartika (UI Scholars Hub, 2024)
Length of stay (LOS) can increase hospital rates and become a cost issue for patients, potentially resulting in a discrepancy between hospital rates and INA-CBGs rates at the hospital. This study aims to determine the difference between the actual costs and BPJS claim costs for diabetic patients based on the length of stay and class level. The research method is observational with a descriptive approach. The data collection technique used retrospective medical record data from 50 patients. The results showed that the largest average difference between hospital costs and BPJS claim costs was for patients with a length of stay >5 days in the VIP class, amounting to IDR 9,562,850.00 with an average claim of IDR 6,146,000.00. The highest cost was for patients with a length of stay of 1-5 days in Class III, amounting to IDR 110,718,506.00 with a total claim of IDR 107,948,500.00. The discrepancy between hospital rates and INA-CBGs rates was caused by factors such as control, excessive use of drugs, and disease complications. Therefore, measures to control these cost discrepancies include cross-subsidies, adherence to the BPJS E-catalog, medication based on appropriate duration of administration, Clinical Pathway, referral management, as well as financial collaboration with social funds from the Muhammadiyah Zakat Infaq and Shadaqah Institution (Lazismu). The length of hospitalization for diabetes mellitus patients can increase the hospital rates to be paid and have implications for reducing the effectiveness and efficiency of services. Thus, hospital managers need to implement quality control and cost control for hospital services.